2019
DOI: 10.4018/jgim.2019010102
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Paradigm of Health and Mobile Phones

Abstract: This article describes how widespread adoption of mobile technology in healthcare is an innovation that is inevitable today in both developed and emerging markets around the world. Mobile health services (m-Health) act as an effective, accessible and affordable means of providing healthcare knowledge to users directly from providers. Despite such benefits of m-Health services, rapid adoption is not yet occurring, particularly in emerging markets. The main barrier is mostly the cynical behavior of users regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 72 publications
6
73
1
3
Order By: Relevance
“…EE has appeared as the next most vital factor influencing mHealth services usage. In addition to expected usefulness, the young generation in Bangladesh expects less effort to accelerate the adoption rate of mHealth services (Nisha, Iqbal, and Rifat 2019). Similar outcomes with respect to this relationship are evident in several earlier studies in IS interface (Lallmahomed et al 2013;Isabel Maria Macedo 2017).…”
Section: Discussionsupporting
confidence: 67%
“…EE has appeared as the next most vital factor influencing mHealth services usage. In addition to expected usefulness, the young generation in Bangladesh expects less effort to accelerate the adoption rate of mHealth services (Nisha, Iqbal, and Rifat 2019). Similar outcomes with respect to this relationship are evident in several earlier studies in IS interface (Lallmahomed et al 2013;Isabel Maria Macedo 2017).…”
Section: Discussionsupporting
confidence: 67%
“…Facilitating conditions refer to the user perceptions of the availability of the resources and support to utilise a given technology (Venkatesh et al, 2012). Facilitating conditions make the use of technology easier and influence the adoption of mobile technology (Nisha et al, 2019). Venkatesh et al (2003) formulate facilitating conditions construct from the model of PC utilisation (Thompson et al, 1991), perceived behavioural control (Ajzen 1991;Taylor & Todd, 1995) and compatibility (Moore & Benbasat, 1991).…”
Section: Facilitating Conditions (Fc)mentioning
confidence: 99%
“…For example, UTAUT has been used to investigate consumers' use of online shopping platforms [20], electronic banks [21], intelligent robots [22], and social media [23]. Others have applied UTAUT or UTAUT2 models in the medical field to study mobile healthcare [7][8][9], e-health services [10], virtual health communities [11], smart medical services [12], and personal health files [24].…”
Section: User Acceptance and Adoption Of Technologymentioning
confidence: 99%
“…At present, most research on the factors that influence the acceptance of emerging technologies is based on the unified theory of acceptance and use of technology (UTAUT). Studies have found, for example, that factors such as performance expectation, effort expectation, social influence, and convenience affect the adoption of mobile medicine [7][8][9], electronic medical services [10], virtual health communities [11], and intelligent medical services [12]. Compared to previous studies, the present one used both the UTAUT model and the health belief model (HBM) to explore the factors affecting consumers' willingness to use PM.…”
Section: Introductionmentioning
confidence: 99%